2021
DOI: 10.1016/j.hrtlng.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in psychosocial and clinical characteristics in the European Registry for Patients with Mechanical Circulatory Support

Abstract: Background: Not much is known about psychosocial characteristics of men and women receiving continuous flow left ventricular assist devices (CF LVAD). Objective: To investigate gender differences in clinical and psychosocial (demographic, behavioral, psychological) characteristics in CF LVAD recipients. Methods: We analyzed European Registry for Patients with Mechanical Circulatory Support (EUROMACS) data (N=2395, 16.8% women; 2011 to 2017) and compared pre-implant characteristics in men and women intended for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Compared with men, women with an LVAD tended to improve their adherence to the self‐care behaviour such as avoiding kinking, pulling, or moving of the driveline at the exit site. Previous research found that before the COVID‐19 pandemic, women tended to report self‐care problems more often than men 8 . Moreover, during the pandemic, among cardiometabolic patients in Latin America, women reported having healthier eating habits and lower alcohol and tobacco consumption, but exercising less than men 13 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with men, women with an LVAD tended to improve their adherence to the self‐care behaviour such as avoiding kinking, pulling, or moving of the driveline at the exit site. Previous research found that before the COVID‐19 pandemic, women tended to report self‐care problems more often than men 8 . Moreover, during the pandemic, among cardiometabolic patients in Latin America, women reported having healthier eating habits and lower alcohol and tobacco consumption, but exercising less than men 13 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous research found that before the COVID-19 pandemic, women tended to report self-care problems more often than men. 8 Moreover, during the pandemic, among cardiometabolic patients in Latin America, women reported having healthier eating habits and lower alcohol and tobacco consumption, but exercising less than men. 13 Further studies are required to test the significance of the current self-care gender difference.…”
Section: Discussionmentioning
confidence: 99%